THE DYNAMICS OF ANTIGEN SPECIFIC PROLIFERATIVE RESPONSES OF LYMPHOCYTES AT EARLY STAGES OF BOVINE PARATUBERCULOSIS INFECTION - T. Reza Ferasyi; A. P. Koets; J. A. Stegeman; C. L.J.J. Kruitwagen (Jurnal Kedokteran Hewan, 2008)
The present study was aimed to quantify the dynamics of early antigen specific proliferative responses of lymphocytes to (protein) antigens associated with experimentalMycobacterium avium subsp. paratuberculosis (Mp) infection cattle. The data were collected from20 experimentally infected calves, and 10 uninfected control animals, during the first 2 years oftheir lives. Several purified protein derivative antigens (Ppdp, Ppda, and Ppdb), tworecombinant Mp heatshock proteins (Hsp65 and Hsp70) and whole bacteria (sonicated Mpstrain 316F) were used to measure lymphocyte proliferation in a lymphocyte proliferationassay. Data were analyzed using a linear mixed effect (LME) model. The results showedsignificant group and timed effects for all antigens tested. At several time points, the responsesin the infected group were found significantly higher as compared to control group. The Ppdantigens induced similar lymphocyte proliferation patterns, as compared to whole bacteriaantigen and Hsp70. These results indicated that the antigen specific proliferative responses oflymphocytes differs for different antigens, probably related to differences in their availabilityduring different stages of infection. The application of LME model is a useful tool for analyzingthe quantitative longitudinal datasets. Keywords: dynamics, Mp, antigen, LME